THE DEPENDENCE OF THE WATER TEMPERATURE OF THE RIVERS OF THE REPUBLIC OF ARMENIA UPON THE AIR TEMPERATURE (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The dependence of the temperature of the water of the rivers is discussed in the work. The mentioned linear equations of dependence have been made for the rivers having different feeding and for all hydrological regions of the Republic of Armenia for the purpose of revealing it. They are of great practicBal importance and can be used to determine the water temperature of the rivers which are poorly investigated or not investigated at all.
Keywords: Republic of Armenia; temperature of the water of the rivers; dependence of the temperature